An ultra-wide band MIMO antenna system with enhanced isolation for microwave imaging applications - Kiani, Saad Hassan; Savcı, Hüseyin Şerif; Munir, Mehr E.; Sedik, Ahmed; Mostafa, Hala (MDPI, 2023)
This paper introduces a novel two-port ultra-wideband (UWB) multiple-input multiple-output (MIMO) antenna system with enhanced isolation characteristics. The antenna, designed on a thin 0.787 mm RO5880 substrate, achieves a compact form factor of 52 × 26 mm (Formula presented.) and offers a wide bandwidth of 9.2 GHz (2.3 GHz to 11.5 GHz) while meeting the VSWR 2:1 criterion. Notably, the proposed antenna demonstrates an impressive increase in isolation, up to 16 dB, through the integration of a shared radiator with small rectangular slots, effectively reducing interference and improving overall performance. Furthermore, a comprehensive analysis of additional MIMO performance parameters, including the envelope correlation coefficient (ECC) and diversity gain, confirms their satisfactory limits, validating the potential of the proposed UWB-MIMO antenna for various UWB applications. The time domain analysis of the UWB antenna is also analyzed, and results are found to be within satisfactory limits. Simulation and measurement results further support the practicality and effectiveness of the antenna design, highlighting its compact size, wide bandwidth, and enhanced isolation characteristics, positioning it as a promising solution for advanced UWB microwave imaging systems.
Keywords: Mmwave; MIMO System; ECC; Gain; Efficiency; Pattern Diversity